2019
DOI: 10.3390/app9245470
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Properties of Aerospace Alloy Elektron 21 Using Boron Carbide Nanoparticles as Reinforcement

Abstract: In this study, the effect of nano-B4C addition on the property profile of Elektron 21 (E21) alloys is investigated. E21 reinforced with different amounts of nano-size B4C particulates was synthesized using the disintegrated melt deposition technique followed by hot extrusion. Microstructural characterization of the developed E21-B4C composites revealed refined grains with the progressive addition of boron carbide nanoparticles. The evaluation of mechanical properties indicated a significant improvement in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The reason for this is due to the formation of thermally unstable secondary phases; this indicates that the presence of thermally stable secondary phases is an important factor to improve ignition resistance. Previous studies on the ignition properties of magnesium-based nanocomposites have shown the enhancement of magnesium's ignition resistance due to the use of thermally stable reinforcements such as B 4 C, Sm 2 O 3 and CeO 2 nanoparticles [16,23,24]. In the current study, a further increase in ignition temperature from 692 • C in the Mg1Ca1Sc alloy to 752 • C in the Mg1Ca1Sc/B 4 C composite was observed (Figure 5).…”
Section: Compressive Propertiessupporting
confidence: 67%
See 3 more Smart Citations
“…The reason for this is due to the formation of thermally unstable secondary phases; this indicates that the presence of thermally stable secondary phases is an important factor to improve ignition resistance. Previous studies on the ignition properties of magnesium-based nanocomposites have shown the enhancement of magnesium's ignition resistance due to the use of thermally stable reinforcements such as B 4 C, Sm 2 O 3 and CeO 2 nanoparticles [16,23,24]. In the current study, a further increase in ignition temperature from 692 • C in the Mg1Ca1Sc alloy to 752 • C in the Mg1Ca1Sc/B 4 C composite was observed (Figure 5).…”
Section: Compressive Propertiessupporting
confidence: 67%
“…In the case of the Mg1Ca1Sc/B 4 C composite, the particle reinforcement caused a 58% reduction in grain size in relation to the Mg1Ca1Sc alloy, and 92% reduction in relation to Mg. This clearly shows that the fine B 4 C particulates had a strong capability in grain growth restriction through the classical grain-boundary pinning mechanism [15,16]. In addition, the homogeneous grain-distribution pattern was attained (Figure 4d) as a consequence of microstructural homogeneity, in terms of good second phase distribution in the composite (Figures 1c and 2c).…”
Section: Grain Morphology/distributionmentioning
confidence: 76%
See 2 more Smart Citations